(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this paper author is trying to review, different methodologies available for MRI segmentation. Here various methodologies are discussed in great detail; moreover this paper will also try to give an elaborate scenario of all the methodologies presented in few popular researches. Few methods discussed here are diffusion weighted and diffusion tensor MRI to white matter diseases, atlas based segmentation, automatic segmentation methods, short axis cardiac images segmentation. Author is trying to discuss all different methodologies mention. The sole objective of this paper is to carry a systematic review of the available literature and to assess the various automatic segmentation techniques.